THE EFFECT OF HISTOCOMPATIBILITY-2 TYPE ON RESPONSE TO THE FRIEND LEUKEMIA VIRUS IN MICE - Lilly, Frank (The Rockefeller University Press, 1968)
Two types of quantitative response to the F-B strain of Friend virus in segregating generations of a cross involving a susceptible (DBA/2 or BALB/c; H-2 (2)) and a resistant (C57BL/6; H-2 (b)) mouse strain show a marked correlation with the H-2 type of the mice. Essential susceptibility, as determined by the splenomegalic response to high virus doses, is controlled by a single pair of alleles which segregates independently with respect to the H-2 locus. However, relative susceptibility, as determined by the incidence of the splenomegalic response at moderate or low levels of virus dosage, is significantly greater among mice homozygous or heterozygous for the H-2 (d) allele than among H-2 (b) homozygotes in these populations. In addition, the incidence of recovery from splenomegaly induced by a given level of virus dosage is significantly greater in H-2 (b) homozygotes than in segregants of other H-2 types among their littermates. Possible mechanisms responsible for these effects are discussed.